2022
DOI: 10.34172/ajehe.2022.04
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Municipal Solid Waste Landfill on the Quality of Water Resources in Khalkhal: A Case Study

Abstract: Transmission of leachate from municipal solid waste landfills can potentially threaten ecosystems and human societies when the landfill has no system for collecting and treating leachate. Leachate produced from landfills finds its way through the soil to groundwater and surrounding surface waters, leading to pollution of water resources. This study aimed to investigate the effects of leachate from Khalkhal landfill (a city in Ardabil province, northwestern Iran) on the quality of groundwater and surrounding su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…septic tanks, landfills) has also been found to be a factor in the spread of coliform bacteria [11,21,22]. However, several studies state that there is no correlation between distance and the spread of coliform bacteria [23]. It is caused by several factors such as soil conditions, rainfall intensity, pH, temperature, groundwater flow, and geology [24].…”
Section: Water Qualitymentioning
confidence: 99%
“…septic tanks, landfills) has also been found to be a factor in the spread of coliform bacteria [11,21,22]. However, several studies state that there is no correlation between distance and the spread of coliform bacteria [23]. It is caused by several factors such as soil conditions, rainfall intensity, pH, temperature, groundwater flow, and geology [24].…”
Section: Water Qualitymentioning
confidence: 99%
“…They emphasized that landfill leachate can greatly change the levels of harmful compounds in river waters. In a case study by Javanmardi et al (2022), the researchers examined the influence of municipal solid waste landfill on water resources in Khalkhal. The study revealed that landfill leachate can cause water pollution, however the extent of its effects on drinking and agricultural uses can vary.…”
Section: Introductionmentioning
confidence: 99%